PENERAPAN HIERARKI MAKNA DALAM UPAYA MENINGKATKAN PEMAHAMAN DISTRIBUTOR PADA PRODUK PEMURNI AIR BMP 1000 - Tatik Purwaningsih (Jurnal Sosial Humaniora dan Pendidikan, 2022)
This study aims to find out How Application Hierarchy of Meaning in an effort to improve understanding of the distributor In Water Purification Products BMP 1000. Results from this study is that with the implementation of CMM / Hierarchy Meaning in improving the understanding of personal selling distributor conversation that includes content, speech act, episode, relationship, life script and cultural patterns in BMP water purification products in 1000 will result in an improved understanding of the distributor of products and the company. Things to be aware of the six elements of the hierarchy of meaning in understanding water purification products distributor in the 1000 BMP is the importance of the episode, the script lives and relationships of the distributor. From the research hierarchy of three elements is very important and has a very large role in the success of improved understanding perusahaan.Unsur distributors on products and other elements such as content, speech act, and cultural patterns supporting factors three and can not be separated from the six elements of the hierarchy of meaning such as a unity of coordination interrelated and influence in increasing the understanding of the product and company.